The new issue puzzle in Malaysia : performance and earnings management / Rashidah Abdul Rahman and Wan Razazila Wan Abdullah - Abdul Rahman, Rashidah; Wan Abdullah, Wan Razazila (Faculty of Accountancy, 2005)
The current study seeks to answer the puzzle as to why firms issuing equity produce poor returns to investors in the long run by exploring whether the post issue performance is being influenced by the potential opportunities of earnings management during the period prior to public listing. Using a sample of 187 IPO firms, results in the study shows that firms that go public over the period 1989-1998 obtained significant negative share return relative to their control firms in the long run. Further analysis provides evidence that managers of Malaysian IPO firms manage their earnings prior to public listing. However, no significant relation is observed between prior earnings management and post issue long run performance. The result is robust with respect to IPO firms with either high or low level of earnings management. Thus, there is no evidence to suggest that the pre offering earnings management is able to predict the negative share return performance post issue. The decline in the post offering share price may be the result of price correction by investors on their beliefs of future earnings based on unfavourable earnings revealed over time by media, analysts reports and subsequent financial statements after listing.